Ediacaran extension along the northern margin of the Yangtze Platform, South China: Constraints from the lithofacies and geochemistry of the Doushantuo Formation. (February 2020) - Wang, Han; Li, Zhiwu; Liu, Shugen; Ran, Bo; Song, Jinmin; Li, Jinxi; Ye, Yuehao; Li, Nan
Abstract: The Ediacaran Doushantuo Formation (Fm) of the Yangtze Platform provides excellent sedimentary records of the Precambrian tectonic evolution of the South China Block related to the final breakup of the Rodinia supercontinent. However, little is known about its sedimentary structural evolution on the northern margin of the Yangtze Platform. This paper presents a detailed lithofacies description and geochemical analysis on the Doushantuo Fm in the vicinity of Chengkou at the northern margin of the Yangtze Platform, in order to understand its tectonic setting and paleogeography. Abrupt variations in stratal thickness and lithofacies over a narrow area, abundant gravity-driven sedimentary structures, and distributions of phosphorite and manganese deposits suggest that both sides of the Chengkou sub-basin were dominated by shallow-water to slope environments, while the center of this sub-basin featured a deep-water environment. Geochemical indicators reveal a clear influence of hydrothermal fluid on the Doushantuo Fm in the center of the Chengkou sub-basin, implying strong synsedimentary extensional activity. These characteristics define a southwest-oriented deep-water subsidence zone (Chengkou sub-basin) that is approximately perpendicular to the strike of the northern margin of the Yangtze Platform. Combined with previous studies, our results indicate that the northern margin of the Yangtze Platform experienced significant extension during the Ediacaran period, which is suggested to be related to the latest breakup of the Rodinia, resulting in the occurrence of alternating uplifts and depressions in a pattern like that of a horst-graben suite. Such widespread extensional activity might have affected the whole Yangtze Platform, with sub-basins like Chengkou extending into its interior, which is of great significance to hydrocarbon exploration. Highlights: Abrupt variations in lithofacies and thickness of Doushantuo Formation, Yangtze Platform. Obvious hydrothermal sediments in the center of sub-basin. The extensional sub-basin might extend into the interior of the Yangtze Platform. Extension is related to the breakup of Rodinia and is of significance for hydrocarbon exploration.